Evaluation and availability of rural properties in the Brejo Paraibano microregion (Research, Society and Development, 2021)
The rural property has this name because those who live in that property live on what theyproduce, whether for their own consumption or for trade, regardless of the size of their production, live specifically from the exploitation of the land. The objective of this work was to present the evaluation methods for the purchase and sale of small rural properties, without the use of technical criteria, adopting only the methods of visual and empirical evaluation. The study was carried out in Pilões, Bananeiras and Areia, which belongs to the Brejo Paraibano Microregion. For data collection, semi-structured questionnaires were elaborated and applied, which contained questions about the ways of evaluating the property value, and which attributes could alter the possible purchase and sale value of the properties, they were applied with farmers from the rural zone We note that of the ten properties that are for sale in the three cities consulted in Brejo Paraibano, 60% are being sold by brokers accredited in CRECI / PB, and 40% have no accreditation. The purchase and sale of rural properties in the municipalities of Areia, Bananeiras and Pilões takes place in a holistic way, and the evaluation of the fixed value of the property does not follow any standard norm or pre-established criteria of evaluation, however traditional methods are used to evaluate and quantify the property of interest, water, vegetation and buildings are a big differentiator when choosing a property as well, as the value attributed to it.